2013
DOI: 10.1007/s11999-013-3098-0
|View full text |Cite
|
Sign up to set email alerts
|

Which Patients Are at Risk for Kidney Dysfunction After Hip Fracture Surgery?

Abstract: Many patients at risk for postoperative KD can be identified and treated. Most patients recover from their KD and the majority return to full weightbearing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 28 publications
0
8
1
Order By: Relevance
“…The only differences were an increased risk of pressure ulcers and increased congestive heart failure and renal failure at 24 months followup, comparisons that were unavailable to us owing to specifics of the ACS-NSQIP 1 database. Finally, the findings of our study are in contrast to those of some studies that have associated diabetes with an increased risk of renal complications, readmission, and mortality after hip fracture surgery [1,14,17]. However, as an example, the study that identified an increased risk of kidney disease in patients with diabetes used an increase of 0.3 mg/dL in creatinine as criteria for postoperative kidney disease.…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…The only differences were an increased risk of pressure ulcers and increased congestive heart failure and renal failure at 24 months followup, comparisons that were unavailable to us owing to specifics of the ACS-NSQIP 1 database. Finally, the findings of our study are in contrast to those of some studies that have associated diabetes with an increased risk of renal complications, readmission, and mortality after hip fracture surgery [1,14,17]. However, as an example, the study that identified an increased risk of kidney disease in patients with diabetes used an increase of 0.3 mg/dL in creatinine as criteria for postoperative kidney disease.…”
Section: Discussioncontrasting
confidence: 88%
“…Previous studies evaluating diabetes and operative stabilization of hip fractures have shown an increased risk of postoperative cardiac complications [10,22], renal dysfunction [10,17], urinary retention [1], extended length of hospital stay [22], and hospital readmission within 28 days [14]. Although all valuable contributions, many of these investigations were limited by small sample sizes, restriction to a single-hospital system, or lack of postdischarge followup.…”
Section: Introductionmentioning
confidence: 99%
“…In a similar study also using the ACS NSQIP 1 database, diabetes was not a risk factor for increased 30-day minor, major, or total morbidity, or 30-day mortality [9]. The authors' findings contrast with other hip fracture series [1,3,5,6,8] where diabetes was associated with increased perioperative complications. Additionally, several studies within the joint arthroplasty literature have found that elevated long-term blood glucose levels, as measured by Hemoglobin A1c, closely correlate with short-term complications [4,7,11].…”
mentioning
confidence: 57%
“…In addition, patients with type 2 diabetes mellitus (T2DM) are reported to have a higher HFx risk compared with patients without DM for a given age and bone mineral density or for a given Fracture Risk Assessment Tool score 22. Several studies have evaluated DM and surgical management of HFx23–28; however, the impact of DM on the postoperative outcome in patients with HFx remains controversial.…”
Section: Introductionmentioning
confidence: 99%